EVALUATION OF THE AMMONIA AIR POLLUTION AND CLIMATIC FACTORS INTERACTIONS, CASE STUDY 2008 BACAU CITY ROMANIA - DOINA CAPȘA; NARCIS BÂRSAN; VALENTIN NEDEFF; EMILIAN MOȘNEGUȚU; DANA CHIȚIMUȘ (Journal of Engineering Studies and Research)
Atmospheric pollution present interest for monitoring and analysis when one or more substances or mixture of pollutants are present in the atmosphere in quantities or for a period that can be dangerous for humans, animals or plants and contribute to endangering the activity or welfare of persons. The present research was aimed to establish a link between meteorological factors (temperature, wind, atmospherically humidity, solar radiation, air pressure) and the ammonia air pollutant. Particularities of research methodology consisted in establishing a connection between meteorological factors in Bacau area and its air quality, taking into account both direct and inverse effects induced by geographical complexity and economic activities. The correlations between ammonia air pollution and analyzed climatic factors variation were realized by graphical interpretations and observing the appropriate links of dependency. In one of the case (2008.08.20) a better dispersion of pollutants occurs in the case of sunshine duration over a longer period, without or with low nebulosity.